2017
DOI: 10.17261/pressacademia.2017.394
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and productivity of Turkish securities firms: 2011-2015

Abstract: Employing a Data Envelopment Analysis (DEA) approach, we investigate the technological progress, efficiency, and productivity of the Turkish securities firms between 2010 and 2015. After measuring the performance of these firms with DEA analysis, we combine the efficiency scores with contingency factors (ownership, size and bank affiliation) in a panel regression analysis in order to determine the effects. Our results indicate that the securities industry in general is less efficient than the existing technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These results imply that increasing the capital size and involving strategic shareholders could boost income and profitability for securities companies. Tas and Cevikcan (2017) utilized Data Envelopment Analysis (DEA) and panel data regression to evaluate technological advancement, efficiency, and productivity of securities firms in Turkey from 2010 to 2015. The outcomes indicated that the securities industry, in general, is less efficient compared to available technology.…”
Section: Research Overview and Theoretical Foundationmentioning
confidence: 99%
“…These results imply that increasing the capital size and involving strategic shareholders could boost income and profitability for securities companies. Tas and Cevikcan (2017) utilized Data Envelopment Analysis (DEA) and panel data regression to evaluate technological advancement, efficiency, and productivity of securities firms in Turkey from 2010 to 2015. The outcomes indicated that the securities industry, in general, is less efficient compared to available technology.…”
Section: Research Overview and Theoretical Foundationmentioning
confidence: 99%